2021
DOI: 10.3389/fmolb.2020.614258
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence for the Future Radiology Diagnostic Service

Abstract: Radiology historically has been a leader of digital transformation in healthcare. The introduction of digital imaging systems, picture archiving and communication systems (PACS), and teleradiology transformed radiology services over the past 30 years. Radiology is again at the crossroad for the next generation of transformation, possibly evolving as a one-stop integrated diagnostic service. Artificial intelligence and machine learning promise to offer radiology new powerful new digital tools to facilitate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 52 publications
0
35
0
1
Order By: Relevance
“…Previous research has established that diagnostic easiness is a fundamental attribute for occupied non-specialist clinicians [ 53 ]. Studies in radiology [ 54 ], ophthalmology [ 55 ], and cardiology [ 56 ] have shown that ML methods may contribute to improving the medical service by AI-assisted workflow. The present study confirms and extends these findings to respiratory physiology showing that machine learning algorithms help diagnose respiratory abnormalities in sarcoidosis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has established that diagnostic easiness is a fundamental attribute for occupied non-specialist clinicians [ 53 ]. Studies in radiology [ 54 ], ophthalmology [ 55 ], and cardiology [ 56 ] have shown that ML methods may contribute to improving the medical service by AI-assisted workflow. The present study confirms and extends these findings to respiratory physiology showing that machine learning algorithms help diagnose respiratory abnormalities in sarcoidosis.…”
Section: Discussionmentioning
confidence: 99%
“…Some challenges in neurosurgical care can be circumvented by computer-assisted diagnosis (CAD) and AI. By using a vast amount of anatomical, morphological and connectivity information, AI and CAD can significantly help neuroradiologists and neurosurgeons to make effective and efficient diagnoses, accelerating the triage and hence the workflow to initiate the treatment, reducing the human labour as well as the costs [45] . Multiple studies have demonstrated that door-to-needle times play a crucial role in reducing mortality and improving the prognosis, and obtaining and interpreting radiological images, and the lack of access to neurologists are the major reasons causing delays in delivering emergency treatments for conditions such as stroke [46] [48] .…”
Section: The Role Of Ai In Pre- Intra- and Postoperative Phases Of Neurosurgerymentioning
confidence: 99%
“…In the era of computer-aided diagnosis tools based on machine learning, deep-learning convolutional neural networks (CNN) and their variants have been increasingly used in medical image pattern recognition as integrative instruments to aid radiologists in the correct diagnosis [ 90 ]. In this regard, the same group of He et al [ 91 ] aimed to predict GCTB local recurrence after intralesional curettage using a deep CNN, evaluating pre-surgery MR images, whose results were compared with the same analysis performed by four musculoskeletal radiologists of at least 12 years’ experience.…”
Section: Imaging Contribution In Gctb Managementmentioning
confidence: 99%